Injectable Amphipathic Artesunate Prodrug‐Hydrogel Microsphere as Gene/Drug Nano‐Microplex for Rheumatoid Arthritis Therapy. (24th August 2022) - Li, Chao; Du, Yawei; Lv, Hongzhi; Zhang, Jun; Zhuang, Pengzhen; Yang, Wu; Zhang, Yingze; Wang, Juan; Cui, Wenguo; Chen, Wei
Abstract: Artemisinin and its derivatives (artemisinins) are first‐line chemotherapeutic agents of lethal malaria, which also showed tremendous value in many other diseases including chronic inflammation. Unfortunately, almost all artemisinins are rapid‐acting medicines with an extremely short half‐life in vivo, which significantly limits their clinical application for these new adaptation diseases. In this study, a locally injectable long‐acting gene/artemisinin co‐delivery nano‐microplex consisting of a biodegradable hyaluronic acid (HA) microsphere and releasable gene/artemisinin co‐delivery nano‐lipoplex is developed first, to obtain an improved efficacy for rheumatoid arthritis (RA). Briefly, a cationic multicomponent drug‐embedded liposome with pharmacological activity is first reported based on two novel artemisinin derivatives (dAPC and dACC), which possess mimic phospholipids and cationic lipids, respectively. A cationic artemisinin‐embedded lipoplex is first reported as a medicative gene carrier here. An in situ injectable TNF‐α siRNA/artemisinin co‐delivery nano‐microplex (MTAsi@MG) is further prepared by immobilization of TNF‐α siRNA/lipoplex on porous microfluidic HA microspheres. Using this nano‐microplex for intra‐articular injection, the sustaining activity of gene therapy and artemisinin efficacy for RA long‐term treatment is first realized. Undoubtedly, this intra‐articular injectable TNF‐α siRNA/artemisinin co‐delivery nano‐microplex based on dAPC/dACC lipoplex and microfluidic microspheres would be one of the most potent gene/drug co‐delivery systems for RA therapy. Abstract : A novel artemisinin‐based gene/drug nano‐microplex (MTAsi@MG) is developed for an articular cavity in situ injection to treat rheumatoid arthritis, which combines with novel artemisinin prodrugs (dACC and dAPC) based gene/lipoplex and microfluidic technology. In vitro and in vivo rat ankle joint injection of MTAsi@MG can continuously reduce the inflammatory response in the joint cavity.